Mutation-related differences in exploratory, spatial, and depressive-like behavior in pcd and Lurcher cerebellar mutant mice - Tuma, Jan; Kolinko, Yaroslav; Vozeh, Frantisek; Cendelin, Jan (Frontiers in Behavioral Neuroscience, 2015)
The cerebellum is not only essential for motor coordination but is also involved in cognitive and affective processes. These functions of the cerebellum and mechanisms of their disorders in cerebellar injury are not completely understood. There is a wide spectrum of cerebellar mutant mice which are used as models of hereditary cerebellar degenerations. Nevertheless, they differ in pathogenesis of manifestation of the particular mutation and also in the strain background. The aim of this work was to compare spatial navigation, learning and memory in pcd and Lurcher mice, two of the most frequently used cerebellar mutants. The mice were tested in the open field for exploration behavior, in the Morris water maze with visible as well as reversal hidden platform tasks and in the forced swimming test for motivation assessment. Lurcher mice showed different space exploration activity in the open field and a lower tendency to depressive-like behavior in the forced swimming test compared with pcd mice. Severe deficit of spatial navigation was shown in both cerebellar mutants. However, the overall performance of Lurcher mice was better than that of pcd mutants. Lurcher mice showed the ability of visual guidance despite difficulties with the direct swim towards a goal. In the probe trial test, Lurcher mice preferred the visible platform rather than the more recent localization of the hidden goal.